Efecto fútbol en el mercado financiero colombiano (2017)
This article analyzes the relationship between the scores obtained by the Colombian national soccer team and the COLCAP index in the years between 2002 and 2016. Based on the behavioral economics theory, this relationship may imply an impact that derives from the scores of the team to the mood of investors in the country. Therefore, significant results on this study would imply that investors build expectations of stock returns taking into account their feelings.